Pengaruh Informasi Akuntansi Terhadap Harga Saham Perusahaan Manufaktur Sub Sektor Makanan Dan Minuman Di Bursa Efek Indonesia - Sari, Ida Yunita; Ali, Karnila (Jurnal Manajemen DIVERSIFIKASI, 2023)
This research is located at the IDX Metro Muhammadiyah University (Indonesia Stock Exchange) office. The sample selection method in this research is purposive sampling method with a total sample of 5 companies. The data collection techniques collect data on the company's financial statements during the study period. The data analysis method used is multiple regression with the help of SPSS software for windows.The results showed that 1) Based on the results of data analysis, the coefficient values ​​of Earning Per Share (EPS), Debt to Equity Ratio (DER), Price Earning Ratio (PER) showed an effect on stock prices simultaneously. 2) Based on the results of data analysis Earning Per Share (EPS), Debt to Equity Ratio (DER), Price Earning Ratio (PER) none of them have a significant effect partially on stock prices in manufacturing companies in the food and beverage sub-sector on the IDX